Base Flip in DNA Studied by Molecular Dynamics Simulations of Differently-Oxidized Forms of Methyl-Cytosine - Helabad, Mahdi Bagherpoor (MDPI, 2014)
Distortions in the DNA sequence, such as damage or mispairs, are specifically recognized and processed by DNA repair enzymes. Many repair proteins and, in particular, glycosylases flip the target base out of the DNA helix into the enzyme’s active site. Our molecular dynamics simulations of DNA with intact and damaged (oxidized) methyl-cytosine show that the probability of being flipped is similar for damaged and intact methyl-cytosine. However, the accessibility of the different 5-methyl groups allows direct discrimination of the oxidized forms. Hydrogen-bonded patterns that vary between methyl-cytosine forms carrying a carbonyl oxygen atom are likely to be detected by the repair enzymes and may thus help target site recognition.